OrÇPlat : uma ferramenta de apoio ao projetista - Carvalho, Fábio Victor Ramos de (2022)
Budgeting is a very important step in project planning. It is an indication of the possibility of monitoring a project, anticipating the best options that could lead to greater economic viability. For this budget to be the closest to reality, factors that encompass all the peculiarities, fluctuation plus taxes, direct and indirect cost indices must be used. This factor demands investments prior to the project with the use of software and tools that help the estimator to arrive at these companies, calculated values with less risk in the development of the project. In view of most of these software, these software being viable for some professionals who work by bus on demand, this work can develop an online platform to help or works. OrÇPlat was developed using HTML, CSS and JavaScript as languages, so that it presents a layout that is easy to understand and fill in data by the listener. The tool proved to be able to download text files, upload and read text files, insert files by the user and execute pre-defined files in code. A case was created to evaluate a study process of an analytical composition of 7.6%, the final result of a reference value S used from the calculated averages, since once a composition is applied from materials combined to materials 78.46%. These values point to success in dishonoring the cost of labor. In this way, it was possible to obtain a system that fits as necessary for the estimators, having an approximate value of reality, having fluctuations according to the prices from labor.